Energy consumption pattern and scalability of routing protocols for heterogeneous MANETs. (2017) - Rishiwal, Vinay; Yadav, Mitul; Kumar, Sandeep
Routing proposals in MANETs have been implemented and tested considering homogeneous environment where nodes have equal capabilities and responsibilities to perform. These assumptions are not helpful to realise the actual performance of the routing protocols. Therefore, existing routing protocols should be tested and benchmarked for heterogeneous MANETs (H-MANETs). In this paper, an analysis of AODV, DSR, AOMDV and CBRP protocols is done. The efficacy of these protocols has been judged for varying network size and varying traffic for H-MANETs. Heterogeneity has been introduced in terms of different random initial energy values given to each node. The performance analysis has been done using network simulator (NS-2) for various important performance parameters. Results show that CBRP as compare to other protocols performs better and as a second choice, especially for large traffic, AOMDV is the best protocol. This work is useful for the judicious and sensible selection of the base routing protocol.